SANKSI PIDANA TERHADAP PELAKU TINDAK PIDANA PENGANIAYAAN DENGAN RENCANA TERLEBIH DAHULU YANG MENGAKIBATKAN KEMATIAN ( PUTUSAN NO. 137 / PID. B / 2021 ): Criminal Sanctions Against People Of Criminal Acts Of Abuse With Preplanning That Result In Death (Rule of No. 137/Pid.B /2021) - Hutabarat, Nivi Esther Fitriayu; Multiwijaya, Vientje Ratna (AMICUS CURIAE, 2024)
Maltreatment with premeditation is defined as the intentional infliction of bodily harm with the knowledge that the victim would suffer catastrophic injuries or die as a consequence (Decision of Kotabaru District Court No. 137/PID.B/2022/PN.KTB). The primary questions that arise are as follows: 1) Is it permissible to punish those who commit the crime of abuse with premeditation that results in death in accordance with Article 351 paragraph 3? Decision No. 137 / Pid. B / 2021 / PN.Ktb entails a jail term of 2 years and 6 months; the question is whether or not this term of imprisonment is appropriate given the circumstances of the case. Using secondary data gleaned from extensive library research, this study use descriptive analysis to draw qualitative inferences about the topic at hand. The study's findings are as follows: 1) The criminal consequences applied to those guilty of the Crime of Persecution with Prior Plans that Result in Death based on Article 351, paragraph 3, of the Criminal Code are not acceptable. Two years and six months in jail is insufficient to achieve the goals of reformation, restraint, retribution, and deterrence, as determined by the Panel of Judges, hence a longer sentence is warranted. The study's findings are linked to the 3R + 1D theory of punishment, suggesting that those responsible should be tried under the provisions of Criminal Code Article 353, paragraph 3, for the crime of persecution with premeditation that ends in death.